Sintesis Komposit Resin-Gd2O3 Untuk Aplikasi Perisai Radiasi Neutron - Rohmad Salam; Agus Salim Afrozi; Auring Rachminisari; Budhi Indrawijaya; Agus Sudjatno; Sulistioso Giat Sukarya (Jurnal Ilmiah Teknik Kimia, 2023)
Synthesis of resin composites with Gd2O3 filler for neutron radiation shielding applications has been carried out. The material used as a neutron shield is a resin which is added 10%, 20%, and 30% Gd2O3. Resin and Gd2O3 were mixed using a mixer for 1 hour and then a catalyst was added as a resin hardener. The mixture is then put into a mold with an inner diameter of 24.5 mm, an outer diameter of 30 mm, and a height of 25 mm. The prints were dried for 3 hours. The results of characterization with SEM at 1000x magnification show that the sample surface is quite compact and dense and does not show pores. The results of the EDS test showed that in the resin sample with the addition of higher Gd2O3, there was an increase in the percentage of Gd in the sample. The results of the compressive test using the Universal Tensile Machine showed that the compressive strength on pure resin without Gd2O3 was 5167 N, on resin with the addition of 10% Gd2O3 was 5088 N and on resin with the addition of 20% Gd2O3 was 1088 N while on resin with the addition of 30% Gd2O3 of 612 N. It can be seen that with the addition of Gd2O3 to the resin there is a decrease in its ability to withstand pressure.